2023
DOI: 10.1038/s41467-023-43118-0
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven discovery of electrocatalysts for CO2 reduction using active motifs-based machine learning

Dong Hyeon Mok,
Hong Li,
Guiru Zhang
et al.

Abstract: The electrochemical carbon dioxide reduction reaction (CO2RR) is an attractive approach for mitigating CO2 emissions and generating value-added products. Consequently, discovery of promising CO2RR catalysts has become a crucial task, and machine learning (ML) has been utilized to accelerate catalyst discovery. However, current ML approaches are limited to exploring narrow chemical spaces and provide only fragmentary catalytic activity, even though CO2RR produces various chemicals. Here, by merging pre-develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…For example, Cu(100) was found to be easier for C-C coupling by combining electrochemical tests and DFT calculations [31]. In situ Raman was performed recently, confirming that higher surface coverage of adsorbed *CO on the Cu (110) surface promotes the formation of the *OCCO and *CH 2 CHO intermediates to generate C 2 products; comparatively, the Cu (111) surface possessed low *CO coverage to produce CH 4 [32]. In recent research, a product-specific active site for ECR was concluded by means of detailed analysis on nine single-crystal copper surfaces.…”
Section: Crystal Facet Regulationmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, Cu(100) was found to be easier for C-C coupling by combining electrochemical tests and DFT calculations [31]. In situ Raman was performed recently, confirming that higher surface coverage of adsorbed *CO on the Cu (110) surface promotes the formation of the *OCCO and *CH 2 CHO intermediates to generate C 2 products; comparatively, the Cu (111) surface possessed low *CO coverage to produce CH 4 [32]. In recent research, a product-specific active site for ECR was concluded by means of detailed analysis on nine single-crystal copper surfaces.…”
Section: Crystal Facet Regulationmentioning
confidence: 98%
“…Due to the distinct arrangement of surface atoms and the resulting interaction with reaction molecules, different crystal facets of the catalysts tend to present varied performance toward ECR [28]. The first ECR on single-crystal Cu was performed by Frese, who found increasing CH 4 generation on Cu(100), Cu (110), and Cu (111) surfaces [29]. In 2002, Hori et al systematically studied the important impact of Cu facets toward specific ECR products, including CH 4 , C 2 H 4 , CH 3 COOH, CH 3 CHO, and C 2 H 5 OH [30].…”
Section: Crystal Facet Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This iterative process could be accelerated using new machine learning approaches that combine DFT models with material science libraries to predict catalyst designs with desirable properties. 86 Once optimal catalysts have been identified, approaches such as permselective coatings may be applied overtop of the CO 2 -RR catalysts to block impurities while allowing efficient transfer of reactants ( i.e. CO 2 ) to the electrode interface.…”
Section: Future Outlook For Co2 Conversion Nanomaterialsmentioning
confidence: 99%
“…Comprehensive studies across various TM X-ide compositions have provided valuable insights. , Controlling variables such as the catalytic support, morphology, and catalyst loading allows for focused investigation of specific parameters, for example, the impact of nonmetal size on the reconstruction and OER performance. Furthermore, researchers can draw on previous efforts to develop materials databases for other classes of materials, such as halide perovskites, transition-metal dichalcogenides and oxides, catalysts for electrochemical CO 2 reduction, , and the Open Catalyst 2022 (OC22) data set for oxide electrocatalysts …”
Section: Perspectives and Research Directionsmentioning
confidence: 99%